2021
DOI: 10.1007/s10571-021-01134-y
|View full text |Cite|
|
Sign up to set email alerts
|

Tat-NTS Suppresses the Proliferation, Migration and Invasion of Glioblastoma Cells by Inhibiting Annexin-A1 Nuclear Translocation

Abstract: Prevention of the nuclear translocation of Annexin-A1 with Tat-NTS (Trans-activator of transcription (Tat), nuclear translocation signal (NTS)) has recently been reported to alleviate neuronal injury and protect against cerebral stroke. However, the role that Tat-NTS plays in the occurrence and development of glioma still needs to be elucidated. Therefore, human glioma U87 cells were treated with various concentrations of Tat-NTS for 24 h, and cell proliferation, migration and invasion were determined with CCK… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…ANXA1 has been extensively studied in gastric cancer and breast cancer ( Maschler et al, 2010 ; Cheng et al, 2012 ). Some studies in gliomas have shown that ANXA1 is a risk prognostic factor ( Xu et al, 2017 ; Luo et al, 2021 ; Wei et al, 2021 ) Therefore, we investigated the expression, prognosis, and related mechanisms of ANXA1 using a public database to provide new markers and potential therapeutic targets for glioma patients.…”
Section: Introductionmentioning
confidence: 99%
“…ANXA1 has been extensively studied in gastric cancer and breast cancer ( Maschler et al, 2010 ; Cheng et al, 2012 ). Some studies in gliomas have shown that ANXA1 is a risk prognostic factor ( Xu et al, 2017 ; Luo et al, 2021 ; Wei et al, 2021 ) Therefore, we investigated the expression, prognosis, and related mechanisms of ANXA1 using a public database to provide new markers and potential therapeutic targets for glioma patients.…”
Section: Introductionmentioning
confidence: 99%
“…RNF12 is involved in down-regulation of RB1 and induces MAPK in GBM progression [ 88 ]. Tat-NTS is suggested to be involved in preventing nuclear translocation of annexin-A1 for carcinogenesis [ 89 ].…”
Section: Lncrnas In Proliferation and Invasionmentioning
confidence: 99%
“…Eriodictyol, a natural flavonoid, can suppress GBM cell migration and invasion by downregulating the PI3K/AKT/NF-κB pathway [ 102 ]. Tat-NTS is a synthesized small molecular peptide that represses annexin-A1 (ANXA1) nuclear translocation, and it can suppress GBM cell migration and invasion by diminishing the phosphorylation level of p65 [ 103 ]. Fentanyl can inhibit p65 activation to decrease the invasiveness of GBM cells [ 104 ].…”
Section: Nf-κb Activation Is Involved In Development and Progression ...mentioning
confidence: 99%